Altai provincial Union of war crippled (1918–1920) - K. A. Tishkina (Омский научный вестник: Серия "Общество. История. Современность")
The development of charity in Russia is increasingly reflected in contemporary Russian historiography. The military-revolutionary period of 1914–1920, associated with large-scale social cataclysms, in this respect it is especially relevant. The study of regional specifics is important for the disclosure of the problem. The purpose of the study is to reveal, using the example of the Altai provincial of war crippled (AlthrovUC), the peculiarities of the formation and activity of public associations under the conditions of the Russian Civil War in Siberia that provided support to disabled people of the First World War (training, employment, social care and adaptation, etc.). The source base of the work is the unpublished sources from the collections of the State Archives of the Altai Territory and materials of the West Siberian press, which are first introduced into scientific circulation. The anthropological approach and the theory of social adaptation became the methodological basis of the work. The author concludes that, despite the difficult conditions of the Russian Civil War (general financial and social crisis), AlthrovUC employees made a significant contribution to supporting the disabled of the First World War.